Craniosquise with Meningocelis in Newborn Calf - Boscarato, André Giarola; Pacheco, Filipe Correa; Orlandini de Andrade, Carla Faria; Jardim, Giovanna Fernanda; de Oliveira, João Antonio Berta; Ribeiro, Rita de Cássia Lima; Belettini, Salviano Tramontin; Alberton, Luiz Romulo (Acta Scientiae Veterinariae, 2020)
Background: Cranioschisis is a malformation that occurs during embryological development and results in incomplete closure of the skull, leaving an opening through which the intracranial tissue can project. Meningocele consists of herniation of the meninges containing cerebrospinal fluid through the cranial defect. In cattle, this association usually manifested by the appearance of a floating saccular protrusion of variable size and volume in the frontal or parietal region of the cranium. This manuscript aims to report a case of cranioschisis associated with meningocele and neurological deficit in a newborn calf in the northwestern region of the state of Paraná. Case: A 2-day-old crossbred female calf was diagnosed with cranioschisis associated with meningocele in the frontal region of the head. On initial clinical examination, an ovoid mass with floating appearance was observed, extending from the supraorbital curvature of the frontal bone to the end of the nasal bones following the midline. The patient had normal parameters for the species and age and a positive sucking reflex. Neurological examination showed permanent lateral decubitus position, spastic paresis of the thoracic limbs and opisthotonus. Complementary imaging studies, including x-rays and ultrasonography, showed a failure in the frontal bone, approximately 5 cm in diameter. Despite the unfavorable prognosis, surgical reduction was chosen. After drainage of the cerebrospinal fluid, excision of the meningeal sac was continuously performed, exposing the subarachnoid space, showing circular failure in the frontal bone with a diameter of 4.5 cm, making it possible to observe part of the right frontal lobe. We opted for occlusion of the bone defect by covering it with the dura mater. Absorbable 0 catgut suture was applied in a simple continuous pattern for coaptation of the meningeal edges. The technique used proved to be viable, but due to lack of therapeutic response and maintenance of the neurological picture, the animal was euthanized three days after surgery. Discussion: The clinical signs of meningocele are generally observed in newborn calves, and the pathology is not reported in aborted animals, which explains the fact that all cases reported in the literature are of calves born at term. Treatment success is variable. In general, it depends on the absence of neurological symptoms, which are invariably linked to morphological alterations in nervous tissue. Thus, animals with neurological symptoms have poor prognosis and may even die spontaneously. In some cases surgical reduction without the use of grafts, as in this report, was successfully performed. The authors reported covering a 7-cm circular gap in the frontal bone thought coaptation of the meningeal edges using a simple continuous pattern of nylon suture, followed by dehorning. In this case, the animal showed no neurological abnormalities and had a good prognosis. We conclude that the surgical treatment of cranioschisis associated with meningocele in bovine species presented in this report had an unfavorable prognosis. As observed in other cases, when the animals have neurological symptoms the prognosis is bleak, probably due to morphological and functional changes of congenital origin in the nervous tissue, as described in the literature. More case studies are needed to elucidate the etiology and pathogenesis of this disorder in bovines, since the cases described in the literature are not associated with the most commonly reported causes, such as the ingestion of certain plants.